Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Multikultural di SMK - Danny Kurniadi (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The aim of this research is to find out and analyze the implementation of multicultural-based Islamic Religious Education learning. This research method uses library research to collect data from various library sources that are relevant to the research topic. The findings of this research indicate that effective multicultural Islamic Religious Education learning strategies involve recognizing and respecting religious and cultural diversity. Teachers need to have competence in integrating multicultural values in learning and using interactive and participatory methods. This research provides a valuable contribution in developing Islamic Religious Education learning strategies that are inclusive and relevant to multicultural conditions in Indonesia